Just-in-time video transcoding system on heterogeneous high performance computing architectures : doctoral thesis - Piljić, Igor (I. Piljić; Fakultet elektrotehnike i računarstva, 2019)
Latest analysis show that 82% of global IP traffic will be video traffic by 2022. Handling this amount of data is a very challenging task for video content providers. Another factor that highlights this problem is the continuously growing number of different devices that can play video content. With such diversity of devices a single copy of the video cannot match requirements of all playback conditions. Just-in-Time (JiT) video transcoding has one of the key roles in resolving these issues. However, it is an extremely compute-intensive and resource-hungry process.